Dynamic Load Modelling within Combined Transport Trains during Transportation on a Railway Ferry - Lovska, Alyona; Fomin, Oleksij; Píštěk, Václav; Kučera, Pavel (MDPI, 2020)
The development of foreign economic activity of the Eurasian states led to the introduction of rail and ferry transportation. It is important to note that the current normative documentation does not fully cover the issues of transporting combined trains by sea. This can lead to a violation of the traffic safety of both the railway ferry and the transport of containers as part of combined trains by sea. In this connection, we investigated the dynamic loading of a container as part of a combined train when transported by a railway ferry. To ensure the stability of the container relative to the frame, we suggested an improvement of the load-bearing structure of a flat wagon. Additionally, we suggested the use of a viscous linkage between containers with the aim of reducing their dynamic load. To justify the suggested solutions, we carried out a mathematical modelling of the container dynamic load. The calculation was performed in MathCad. Due to the fact that the container has its own degree of freedom when transported by sea, the accelerations were separately determined for the supporting structure of the flat wagon and for the container. We found that the total amount of acceleration that acted on the container was 3.57 m/s2 (0.36 g) and on the load-bearing structure of the wagon was 2.47 m/s2 (0.25 g) which were, respectively, 38% and 23% less than the acceleration values in the typical scheme of their interaction. To determine the fields of acceleration distribution relative to the load-bearing structure of a flat wagon with containers, we carried out computer modelling of their dynamic load. The maximum percentage of discrepancy between the accelerations obtained by mathematical and computer modelling was 17.7%. The study will contribute to the creation of recommendations for the safe transport of combined trains by sea, as well as to increasing the efficiency of combined transport through international transport corridors.

The development of foreign economic activity of the Eurasian states led to the introduction of rail and ferry transportation. It is important to note that the current normative documentation does not fully cover the issues of transporting combined trains by sea. This can lead to a violation of the traffic safety of both the railway ferry and the transport of containers as part of combined trains by sea. In this connection, we investigated the dynamic loading of a container as part of a combined train when transported by a railway ferry. To ensure the stability of the container relative to the frame, we suggested an improvement of the load-bearing structure of a flat wagon. Additionally, we suggested the use of a viscous linkage between containers with the aim of reducing their dynamic load. To justify the suggested solutions, we carried out a mathematical modelling of the container dynamic load. The calculation was performed in MathCad. Due to the fact that the container has its own degree of freedom when transported by sea, the accelerations were separately determined for the supporting structure of the flat wagon and for the container. We found that the total amount of acceleration that acted on the container was 3.57 m/s2 (0.36 g) and on the load-bearing structure of the wagon was 2.47 m/s2 (0.25 g) which were, respectively, 38% and 23% less than the acceleration values in the typical scheme of their interaction. To determine the fields of acceleration distribution relative to the load-bearing structure of a flat wagon with containers, we carried out computer modelling of their dynamic load. The maximum percentage of discrepancy between the accelerations obtained by mathematical and computer modelling was 17.7%. The study will contribute to the creation of recommendations for the safe transport of combined trains by sea, as well as to increasing the efficiency of combined transport through international transport corridors.
Dynamic Load Modelling within Combined Transport Trains during Transportation on a Railway Ferry
Keywords: wagon; carrying structure; combined transportation; dynamics; strength; wagon; carrying structure; combined transportation; dynamics; strength